A gender‐dependent analysis of Cushing's disease in childhood: pre‐ and postoperative follow‐up. (2nd February 2015) - Libuit, Laura G.; Karageorgiadis, Alexander S.; Sinaii, Ninet; Nguyen May, Nina M.; Keil, Margaret F.; Lodish, Maya B.; Stratakis, Constantine A.
Summary Objective To analyse gender differences in the clinical presentation and recovery of paediatric patients with Cushing's disease (CD) after transsphenoidal surgery (TSS). Indeed, gender differences between paediatric patients with CD during presentation, after TSS and postoperative recovery have not been adequately studied. Design Data were obtained and retrospectively analysed from clinical reports and biochemical tests at the time of presentation, 5–9 days after TSS and at the 6 and 12 months postoperative follow‐up visits to determine hypothalamic–pituitary–adrenal axis (HPAA) recovery. Patients Data from 102 paediatric patients (48 females, 54 males, mean age 12·9 ± 3·0) with CD who underwent TSS at the National Institute of Health (NIH) Clinical Center between 1997 and 2011. Results There was equal distribution of paediatric CD between males and females (53% vs 47%; n = 102, P = 0·484). Males were more likely than females to present with higher mean BMI Z‐scores (2·2 ± 0·7 vs 1·9 ± 0·6, P = 0·0079), lower mean height Z‐scores (−1·2 ± 1·3 vs −0·7 ± 1·1, P = 0·0467) and higher median plasma ACTH (12·2 vs 8·5 pmol/l; P = 0·0495). Females did not present more frequently with any single sign or symptom. No significant differences were found between males and females for CD cure rates 5–9 days after TSS (87·0% males vs 87·5% females, P = 1·0), long‐term cure rates (86·5% vs 93·7%; n = 69; P = 0·4374) and HPAA recovery time (11·2 ± 2·5 vs 11·7 ± 2·5 months; n = 47; P = 0·1992). Conclusions Paediatric CD is found to have equal distribution between males and females, but male patients present with elevated BMI and potentially shorter height and higher plasma ACTH. There is no significant difference in the cure rate or HPAA recovery time after TSS between males and females.